QUALITY OF LICENSING SERVICES FROM THE INVESTMENT AND INTEGRATED ONE-STOP SERVICES AGENCY OF NGANJUK REGENCY - Utomo, Wahyu Setyo; Pramono, Teguh; Marwanto, Heru (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2024)
The Investment and Integrated One-Stop Services Agency of Nganjuk Regency is one of the regional government agencies in Nganjuk Regency which is an agency specifically tasked with providing licensing services that directly relate to the community. The Investment and Integrated One-Stop Services Agency of Nganjuk Regency is required to improve the quality of its services. The research method used by researchers is qualitative research with a descriptive research type. The results of the research show that based on Parasuraman's theory, measuring the quality of public services can be viewed from five main dimensions, namely 1) Tangible, 2) Reliability, 3) Responsiveness, 4) Assurance, and 5) Empathy shows that the quality of public services in The Investment and Integrated One-Stop Services Agency of Nganjuk Regency in general it is good. Even though there are deficiencies in the timeliness of services, the provision of service times and there is still discrimination in services to the community.